MENINGKATKAN DAYA MATEMATIK MAHASISWA CALON GURU MATEMATIKA MELALUI PEMBELAJARAN BERBASIS MASALAH - Dadang Juandi, - (2006)
Inadequacy in mathematical power of prospective teachers is a very serious problem in mathematics education. Mathematical disposition is important as well. Both problems are an important education issue in Indonesia and need to be examined more rigorously. This experimental research is focused on efforts to compare the enhancement of mathematical power of middle school prospective teachers as an impact of employment the conventional and problem-based teaming approach. The subjects are fifth semester students who are prospective teachers of mathematics. They study mathematical statistics and are chosen from two different universities. There are two classes chosen in each university, one serving as experimental group and the other as control group, instruments used on this research are of two different kinds of tests, which measure equivalent mathematical power aspects including reasoning, connection, communication, problem solving, representation, Likert attitude scale, observation and interview guideline. Based on data analysis, it is concluded that the problem-based learning approach is significantly enhancing prospective teachers' mathematical power compare to the conventional approach. This conclusion is derived based on the universities' ranks and prior knowledge. Based on responses to the test, it is concluded that the prospective teachers from the experimental class tends to perform better on some tested mathematical competences, i.e. in solving mathematical communication, finding different strategies in solving problems, and conducting mathematical reasoning. Some other competencies that need to be developed are proofing abilities and mathematical connections. Students wtyo study with the problem-based approach show significantly better attitudes on mathematical statistics than those involved in the conventional ones. However, there is no significant difference among prior knowledge group. It is also found that the attitudes of prospective teachers to the problem-based learning approach is highly positive, mainly to the small group discussion sessions.